Malaysia's September 1998 controls : background, context, impacts, comparisons, implications, lessons - Jomo, K. S. (UN New YorkUS, 2005)
Explains the circumstance in which the controls were introduced. Assesses their nature and impact before drawing some general lessons of relevance to other emerging market economies.